Pemenuhan Hak Anak Pasca Perceraian: Analisis Normatif terhadap Putusan Pengadilan Agama - Raudatul Jannah; Mustamin Giling (Al-Kindi, 2026)
Divorce is permissible under Islamic law. A divorce decreed by a religious court does not absolve parents of their obligations to fulfill children's rights, including the right to care, support, education, and protection. In divorce cases, custody of children under 12 years of age typically falls to the mother, with the father obligated to continue supporting the children of the marriage. This study aims to analyze the judge's legal considerations in religious court decisions regarding the fulfillment of children's rights after divorce. The research method used is normative juridical research, focusing on the legal approach and court decisions related to children's rights. Primary data consists of laws and court decisions, while secondary data consists of scientific journals. The results of the study indicate that the fulfillment of children's rights in the context of divorce encompasses a series of decisions and obligations that determine how both parents will participate in fulfilling the children's rights after the divorce. A normative juridical analysis of the judge's legal considerations in court decisions concludes that the judge's legal considerations were conducted comprehensively and based on applicable legal provisions.